2020
DOI: 10.1111/echo.14841
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of exercise‐induced diastolic dysfunction: A systematic review

Abstract: Background: Recent guidelines recommend diastolic stress testing among patients with unexplained dyspnea. Previous studies have reported exercise related change in diastolic parameters as a prognostic marker for worse outcomes. However, the role of exercise-induced diastolic dysfunction (DD) in predicting adverse outcomes has not been fully established. Method: We conducted a meta-analysis to explore the prognostic significance of exercise-induced DD. PUBMED/EMBASE/SCOPUS databases were searched for studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In our study, DSE revealed DD in 21% of patients with HF symptoms and suspected DD or borderline diastolic abnormalities on rest TTE. There is considerable heterogeneity among other studies in the rates of abnormal LV diastolic function on exercise echocardiography related to study groups and various echocardiographic parameters used as markers of diastolic function [15,16]. Therefore, the rates of positive diastolic stress tests varied from a few percent [17] to nearly half of the study group [18].…”
Section: Receiver Operating Characteristic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, DSE revealed DD in 21% of patients with HF symptoms and suspected DD or borderline diastolic abnormalities on rest TTE. There is considerable heterogeneity among other studies in the rates of abnormal LV diastolic function on exercise echocardiography related to study groups and various echocardiographic parameters used as markers of diastolic function [15,16]. Therefore, the rates of positive diastolic stress tests varied from a few percent [17] to nearly half of the study group [18].…”
Section: Receiver Operating Characteristic Analysismentioning
confidence: 99%
“…Finally, DSE was found to predict clinical outcomes. The meta-analysis by Sud et al found that exercise-induced DD was associated with a higher likelihood of cardiovascular mortality or hospitalization [15].…”
Section: Receiver Operating Characteristic Analysismentioning
confidence: 99%
“…Routine supplementation of exercise echocardiography with post‐exercise diastolic measures can improve the prognostic utility of the test. Several studies and one meta‐analysis have demonstrated that exercise‐induced diastolic dysfunction is associated with a higher likelihood of adverse cardiovascular outcomes 2 . The American Society of Echocardiography (ASE) guidelines recommend diastolic stress testing for echocardiographic assessment of exercise hemodynamics in patients with unexplained dyspnea, but studies have suggested the prognostic utility of diastolic measures in a broader group of patients referred for stress echocardiography 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and one meta-analysis have demonstrated that exercise-induced diastolic dysfunction is associated with a higher likelihood of adverse cardiovascular outcomes. 2 The American Society of Echocardiography (ASE) guidelines recommend diastolic stress testing for echocardiographic assessment of exercise hemodynamics in patients with unexplained dyspnea, but studies have suggested the prognostic utility of diastolic measures in a broader group of patients referred for stress echocardiography. 3 The diastolic variables recommended by ASE guidelines include resting septal e' velocity, post-exercise E/e' ratio, and post-exercise tricuspid regurgitant jet velocity, measures that can be routinely obtained during treadmill exercise echocardiography testing in all patients regardless of indication.…”
Section: Introductionmentioning
confidence: 99%
“…5 For this reason, exercise echocardiography has been used to estimate left ventricular filling pressure, pulmonary artery pressure, and the right ventricular–arterial coupling responses to exercise. 6 However, although exercise hemodynamic results are prognostically meaningful, 7,8 there are broad limits of agreement between invasive and noninvasive assessment of filling pressure 9 and pulmonary artery systolic pressure (PASP) 10 with exercise.…”
mentioning
confidence: 99%